2007
DOI: 10.1111/j.1475-097x.2006.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the 1·73‐m2 body surface area normalization: problems and implications

Abstract: A historical review of the origins of body surface area (BSA) determination reveals a number of theoretical and methodological errors, as does the choice of 1 x 73 m(2) as the normal BSA for humans. BSA normalization is justifiable for some physiological variables, e.g. glomerular filtration rate and cardiac output, but not all. However, other normalization indices, in particular extracellular volume, offer theoretical and practical advantages compared with BSA. While the choice of the figure 1 x 73 m(2) is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 15 publications
0
44
0
Order By: Relevance
“…Indeed, equations used to estimate BSA have not been validated in obese individuals and are not stratified by sex (26). Measuring BSA in obese subjects still remains a challenging and unsolved problem, and choosing the best body size descriptor to scale kidney function is difficult (24). Although the Dubois and Dubois formula has already been criticized, we found that BSA and mGFR with another BSA equation (the formula by Livingston and Lee [15]) are not significantly different (Supplemental Table 1) from the results derived from the Dubois and Dubois formula.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, equations used to estimate BSA have not been validated in obese individuals and are not stratified by sex (26). Measuring BSA in obese subjects still remains a challenging and unsolved problem, and choosing the best body size descriptor to scale kidney function is difficult (24). Although the Dubois and Dubois formula has already been criticized, we found that BSA and mGFR with another BSA equation (the formula by Livingston and Lee [15]) are not significantly different (Supplemental Table 1) from the results derived from the Dubois and Dubois formula.…”
Section: Discussionmentioning
confidence: 99%
“…Patients had received tyrosine kinase inhibitors (sunitinib, n ϭ 90; sorafenib, n ϭ 15; axitinib, n ϭ 8) or bevacizumab (n ϭ 3) as first-line treatment for metastatic RCC. Detailed patient information is given in Table 1 [11,12]. VFA and SFA were measured retrospectively on available computed tomography scans performed before treatment initiation, at the level of the umbilicus with the patient in the supine position, as described previously [13].…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…The mean BSA of the entire cohort in the present study was 1.91 m 2 , which is similar to the current mean BSA of 25-year-old males and females in the United States of 1.92 m 2 [42]. In contrast, the current reference BSA is 1.73 m 2 , against which individually measured GFR values were normalized in the development of all the GFR equations considered in the current study [16,17,30].…”
Section: Gentamicin Volume Of Distribution Per Tbw (L Kgmentioning
confidence: 52%